Hydrologic and Environmental Behavior of GeoWaste and Waste Rock in Field Experimental Piles - Mining, Metallurgy & Exploration (2021) - MOHAMMAD R. H. GORAKHKI; Christopher A. Bareither; Joseph Scalia IV; MANUEL APARICIO (Society for Mining, Metallurgy & Exploration, 2021)
The focus of this study was on the evaluation of hydrologic and environmental behavior observed in GeoWaste and waste rock test piles. GeoWaste is a mixture of fast-filtered tailings and waste rock prepared as a tailings-dominated mixture. The two test piles included potentially acid-generating (PAG) waste rock and were operated for 26 months to evaluate whether GeoWaste can suppresses sulfide oxidation and production of metal-rich acid mine drainage relative to PAG waste rock. The test piles were constructed in the shape of truncated 5-m-tall pyramids with 25-m base sides and flat 5-m × 5-m top surfaces. Water content, temperature, electrical conductivity, and oxygen concentration were monitored in four layers and at five locations within each layer in both test piles. In addition, 5-m × 5-m lysimeters were installed at the base of each pile to collect leachate. Approximately 2660 mm of water was added to the surfaces of the test piles via precipitation and irrigation (irrigation ≈ 1050 mm applied at an approximately constant rate for 70 days). The measured saturation, oxygen concentration, electrical conductivity, and temperature in the GeoWaste and waste rock piles suggest more sulfide oxidation occurred in the waste rock pile compared to the GeoWaste pile. Observations from the pile experiments suggest that co-managing mine waste in the form of GeoWaste reduced acid generation compared to waste rock alone due to the lower permeability and unsaturated state of the GeoWaste pile that reduced downward migration of moisture and inhibited drainage.